The Effect of Innovation Barriers and Green Skepticism on Millennials and Gen Z's Intention to Resist Green Baby Care Products in Indonesia - Hamsah, Dian; Wibowo, Mas Wahyu (International Journal Labs, 2025)
As sustainability gains momentum worldwide, green-labeled products are flooding the market, including in the baby care segment. However, adoption is not guaranteed among Indonesian Millennials and Gen Z, despite their environmental awareness. This study investigates why Indonesian Millennials and Gen Z still resist green baby care products by examining how functional and psychological barriers shape consumer decisions. A structured online survey of 222 respondents was conducted, and data were analyzed using PLS-SEM. The results reveal that usage, value, and tradition barriers significantly increase resistance, while risk and image barriers do not. Notably, green skepticism strengthens the effect of the value barrier, meaning that when consumers doubt the truth behind “green” claims, their perception of product value weakens, further amplifying resistance. However, green skepticism does not significantly moderate other types of barriers. This study extends Innovation Resistance Theory by incorporating green skepticism as a moderating factor in the context of baby care, a category rarely examined in previous studies. This integration provides new insights into how skepticism toward sustainability claims can interact with innovation barriers in shaping consumer resistance. These findings call for action: Brands must go beyond labels. To win over today’s critical, connected consumers, companies must not only deliver real value and ease of use, but also improve product visibility and accessibility. In addition, addressing habitual buying patterns and building trust through transparent, evidence-based communication are crucial to reducing resistance and supporting adoption of green innovations, especially among young, discerning parents.